SELLING AND PURCHASING INTERNAL CONROL ANALYSIS AT FORUM BASED E-COMMERCE (Case Study at Kaskus Market Forum) - Nusa, Adikrishna Satria; Hariadi, Bambang (Jurnal Ilmiah Mahasiswa FEB, 2014)
Kaskus Market Forum is one of the popular e-commerce that used in buying and selling things. The purpose of research that was done in Kaskus market forum is to recognize how good the internal control system is. This reseach has descriptive nature and will explain how is the buying and selling procedure in Kaskus Market Forum and howÂ  good the internal control system in Kaskus Market Forum. The result of this reseach show that Kaskus Market Forum already has a good internal control system although it still have some weaknesses. Most of the weaknesses comes from the nature of e-commerce and is a coherent risk on Kaskus Market Forum. This weakness can be covered by increasing the number of moderators and updating the rules of transaction in Kaskus Market Forum. Key words : e-commerce, internal control system, selling and buying forum.